Up-conversion luminescence in low phonon heavy metal oxide glass co-doped with Er3+/Ho3+ - Ragiń, T.; Baranowska, A.; Sołtys, M.; Górny, A.; Zmojda, J.; Kochanowicz, M.; Mikulski, P.; Jadach, R.; Dorosz, D. (Photonics Letters of Poland, 2018)
In this paper, heavy metal oxide glasses co-doped with erbium and holmium ions have been synthesized. Glass composition, based on the bismuth and germanium oxides, has been selected in terms of high thermal stability (delta T = 125 °C), high refractive index (n = 2.19) and low maximum phonon energy (hvmax = 724 cm-1). Up-conversion luminescence spectra under the 980 nm laser diode excitation have been observed as a result of radiative transitions within the quantum energy level structures of Er3+ and Ho3+ ions. Optimization of rare earth ions content has been conducted, the highest emission intensity in the visible wavelength range has been observed in glass co-doped with molar concentration 0.5 Er2O3 / 0.5 Ho2O3. Full Text: PDF References F. Zhang, Z. Bi, A. Huang, Z. Xiao, "Visible luminescence properties of Er3+?Pr3+ codoped fluorotellurite glasses", Opt. Materials 41, 112 (2014). CrossRef S. Li, S. Ye, T. Liu, H. Wang, D. Wang, "Enhanced up-conversion emissions in ZnO-LiYbO2:RE3+ (RE = Er or Ho) hybrid phosphors through surface modification", J. All. Comp. 658, 85 (2016). CrossRef J. Fu, X. Zhang, Z. Chao, Z. Li, J. Liao, D. Hou, H. Wen, X. Lu, X. Xie, "Enhanced upconversion luminescence of NaYF4:Yb, Er microprisms via La3+ doping", Opt. Laser Tech. 88, 280 (2017). CrossRef Y. Tian, R. Xu, L. Hu, J. Zhang, "2.7 ?m fluorescence radiative dynamics and energy transfer between Er3+ and Tm3+ ions in fluoride glass under 800 nm and 980 nm excitation", J. Quant. Spec. Rad. Tra. 113, 87 (2012). CrossRef M. Zhang, A. Yang, Y. Peng, B. Zhang, H. Ren, W. Guo, Y. Yang, C. Zhai, Y. Wang, Z. Yang, D. Tang, "Dy3+-doped Ga?Sb?S chalcogenide glasses for mid-infrared lasers", Mat. Res. Bul. 70, 55 (2015). CrossRef G. Yang, T. Li, "Broadband 1.53 ?m emission in Er3+-doped Ga-Bi-Pb-Ge heavy metal oxide glasses", J. Rare Earths 26, 924 (2008). CrossRef Y. Guo, Y. Tian, L. Zhang, L. Hu, J. Zhang, "Erbium doped heavy metal oxide glasses for mid-infrared laser materials", J. Non-Cryst. Solids 377, 119 (2013). CrossRef Z. Hou, Z. Xue, F. Li, M. Wang, X. Hu, S. Wang, "Luminescence and up-conversion mechanism of Er3+/Ho3+ co-doped oxyfluoride tellurite glasses and glass?ceramics", J. All. Comp. 577, 523 (2013). CrossRef X. Li, Q. Nie, S. Dai, T. Xu, L. Lu, X. Zhang, "Energy transfer and frequency upconversion in Ho3+/Yb3+ co-doped bismuth-germanate glasses", J. All. Comp. 454, 510 (2008). CrossRef S.S. Rojas, J.E. De Souza, M.R.B. Andreeta, A.C. Hernandes, "Influence of ceria addition on thermal properties and local structure of bismuth germanate glasses", J. Non-Cryst. Solids 356, 2942 (2010). CrossRef M.S. Ebrahim, Irina, Mid-infrared coherent sources and applications, Springer (2008). CrossRef T. Ragin, J. Zmojda, M. Kochanowicz, P. Miluski, P. Jelen, M. Sitarz, D. Dorosz, "Enhanced mid-infrared 2.7 ?m luminescence in low hydroxide bismuth-germanate glass and optical fiber co-doped with Er3 +/Yb3 + ions", J. Non-Cryst. Solids 457, 169 (2017). CrossRef K. Biswas, A.D. Sontakke, R. Sen, K. Annapurna, "Enhanced 2 ?m broad-band emission and NIR to visible frequency up-conversion from Ho3+/Yb3+ co-doped Bi2O3?GeO2?ZnO glasses", Spectr. Acta. Part A, Mol. Biomol. Spectr. 112, 301-308 (2013). CrossRef R.S. Romaniuk, D. Dorosz, J. Żmojda, M. Kochanowicz, W. Mazerski, "Upconversion luminescence in tellurite glass codoped with Yb3+/Ho3+ ions", Proc. of SPIE 8903, 890307 (2013). CrossRef